In vitro schistosomicidal activity of triterpenoids from the African plant Momordica balsamina - Ramalhete, Cátia (2012)
Schistosomiasis, also known as bilharzia, is a chronic liver and intestinal parasitic disease caused by trematode worms of the genus Schistosoma. Among the five major species of human schistosomes, Schistosoma mansoni is the most prevalent, being endemic in 54 countries. Praziquantel is the only available drug against all forms of schistosomiasis. The development of praziquantel resistance is a great concern and new drugs are urgently needed [1]. Momordica balsamina L. (Cucurbitaceae), commonly known as African pumpkin, is a vegetable widespread in tropical and subtropical regions that has been used as food, mainly in sub-Saharan Africa. It has also been widely used in traditional medicine in Africa to treat various disease symptoms, mostly diabetes and malaria. In previous work, bioassay-guided fractionation of the methanol extract of the aerial parts of M. balsamina led to the isolation of several cucurbitane-type triterpenoids. Most of the isolated compounds as well their acylated derivatives displayed antimalarial activity [2, 3]. Continuing our search for antiparasitic compounds, the aim of this work was to evaluate the in vitro schistosomicidal activity of several triterpenoids isolated from M. balsamina against Schistosoma mansoni adult worms [4, 5]. Praziquantel was used as positive control.